The Behavioral Patterns and Social Skills of Young Children with/without Disabilities at Home and at School - Meral MELEKOĞLU (Anı Publishing, 2021)
Children with/without disabilities who are in early childhood display specific behavior or social skills depending on their age development. Most children display problem behavior and poor social skills. It is very important to examine the behavior patterns of children for planning early prevention interventions. This study aims to evaluate the problem behavior and social skills level of young children with/without disabilities based on the thoughts of first caregivers, teachers and staff. This research is phenomenological research which is one of the qualitative research method designs. 27 first caregivers, 12 teachers and seven staff participated in the study. This study was conducted at a state kindergarten where inclusive education was implemented. The data were collected using semi-structured individual and focus group interviews. The data were analysed using the descriptive analysis technique. The findings obtained in this study showed that children displayed similar problem behaviors in home and school settings. To the participants, children had many problem behaviors and inadequate social skills in early childhood. These problem behaviors were regarding externalizing, internalizing and antisocial behaviors. As a conclusion, permanent prevention studies are suggested considering the problems which were experienced with the children with/without disabilities in this study.